1990
DOI: 10.1021/es00073a012
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of aniline and other primary aromatic amines by manganese dioxide

Abstract: Financial support from EROS-2000 Project is gratefully acknowledged. We thank J. I. Gomez-Belinchon, R. Llop, and M. Vails for technical assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
262
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(288 citation statements)
references
References 18 publications
23
262
1
2
Order By: Relevance
“…Figure 9 shows the plot of lnC 0 /C against t where, C represents the concentration of MB at time, t, and C 0 represents the initial concentration of MB. The kinetics of the degradation process fitted to the pseudo-first-order kinetics model well which is in good agreement with the earlier works [12,13,42], where the authors reported the oxidative degradation of a number of organic pollutants with Mn oxides. In the present study, the rate constant (k) was found to be 0.0045 min −1 .…”
Section: Kinetics Of Mb Degradationsupporting
confidence: 90%
“…Figure 9 shows the plot of lnC 0 /C against t where, C represents the concentration of MB at time, t, and C 0 represents the initial concentration of MB. The kinetics of the degradation process fitted to the pseudo-first-order kinetics model well which is in good agreement with the earlier works [12,13,42], where the authors reported the oxidative degradation of a number of organic pollutants with Mn oxides. In the present study, the rate constant (k) was found to be 0.0045 min −1 .…”
Section: Kinetics Of Mb Degradationsupporting
confidence: 90%
“…24,25 Manufacturers that produce dyes, cosmetics, medicines and rubber 26 release these types of materials. The degradation of phenyl and phenylcarbamate pesticides 24,27 can also release these compounds. Because of their threat to the environment, a fast analytical method is required.…”
Section: Introductionmentioning
confidence: 99%
“…Mn(III,IV) oxides (Mn oxides) and soluble Mn(III) complexes are the strongest oxidizing agents in the environment after oxygen and play an important role in many biogeochemical cycles (25). At pH 7, they can oxidize metals, catalyze the formation of humic substances and organic nitrogen complexes, and oxidatively degrade humic and fulvic acids to bioavailable low-molecular-weight organic compounds (6,38,40).…”
mentioning
confidence: 99%